Reterritorialising pedagogies of listening: bringing into dialogue culturally responsive pedagogies with Reggio Emilia principles. Issue 1 (2nd January 2023) - Rigney, Lester-Irabinna; Kelly, Stephen
ABSTRACT: Cultural and linguistic diversity in educational settings is the new normal internationally. However, domestic research shows that Indigenous Australian students are still not benefiting from school. Despite global research on Culturally Responsive Pedagogies and Reggio Emilia being proven to work with minoritised groups in settler societies, little research exists in Australia. This paper addresses this noticeable gap in the literature, bringing into dialogue the culturally responsive pedagogy movement with Reggio Emilia principles for theoretical nuanced examination of listening pedagogies. This dialogue seeks to shift epistemological and ontological framings of the child and their schooling experience. The paper argues for a deterritorialising of Indigenous ways of being and knowing that view learning as socially and culturally mediated. A central finding is that culturally responsive Reggio Emilia inspired practice offers educational change through a decolonising frame using instructional dimensions of relational and dialogic teaching. The paper concludes that reductive pedagogy constrains Indigenous listening and learning and that explicitly connecting curriculum to students' cultural strengths is an instructional reform opportunity for reterritorialising pedagogy.